A Market – Based analysis On Small and A Medium Busines Strategies in Bogor’s Footwear Industry - Gen Gen Gendalasari (Kesatuan Press, 2020)
This research aims to fill the existing gap, namely the right coaching model that can be developed for MSME practitioners so that they have competitive advantages. A sustainable coaching model application from the Ciomas footwear MSMEs can be carried out in an integrated, directed and targeted, market-based manner. By using qualitative methods, it is known that the atributes of production process, production equipment, production control, buildings and facilities, markets, quality standardization, business management, financing, and promotion have average performance. In this case based on the perception of the footwear MSMEs, the performance measure is on a medium scale, while the expectation measure is on a high scale.